Anxiety and Food Addiction in Men and Women: Results From the Longitudinal LIFE-Adult-Study - Hussenoeder, Felix S.; Pabst, Alexander; Conrad, Ines; Löbner, Margrit; Engel, Christoph; Zeynalova, Samira; Reyes, Nigar; Glaesmer, Heide; Hinz, Andreas; Witte, Veronica; Schroeter, Matthias L.; Wirkner, Kerstin; et al. (Frontiers in Psychiatry, 2022)
Background: Anxiety is a widespread phenomenon, and it is connected to disordered eating and obesity. We want to analyze the connection between anxiety and food addiction (FA) over two points in time to better understand the directionality of the association. Since there are gender differences with regard to anxiety and eating, we are also interested in differences between men and women. Methods: We used data from the population-based LIFE-Adult-Study (N= 1,474) at time 1 (baseline) and time 2 (first follow-up) to analyze the connections between anxiety (GAD-7) and FA (YFAS) using a multiple group latent cross-lagged panel model with female and male participants as groups. We controlled for age, marital status, socioeconomic status and social support. Results: Anxiety (females: β= .50, p ≤ 0.001; males: β= .59, p ≤ 0.001) as well as FA (females: β= .37, p ≤ 0.001; males: β= .58, p ≤ 0.001) exhibited stability over time for both genders. We found a significant association between anxiety at time 1 and FA at time 2 for women (β= .25, p ≤ 0.001) but not for men (β= .04, p = 0.10), and significant associations between FA at time 1 and anxiety at time 2 for women (β= .23, p ≤ 0.001) as well as men (β= .21, p ≤ 0.001). Conclusion: FA longitudinally affects anxiety, independent of gender and other sociodemographic variables. In addition, anxiety affects subsequent FA as well, but only in women. Interventions that address FA could reduce anxiety in men and women, while interventions that mitigate anxiety could help prevent FA in women.